Development of a high-resolution melt-based assay to rapidly detect the azole-resistant Candida auris isolates - Hamid Morovati; Hamid Badali; Mahdi Abastabar; Keyvan Pakshir; Kamiar Zomorodian; Bahram Ahmadi; Behrouz Naeimi; Sadegh Khodavaysi; Sanam Nami; Esmaeel Eghtedar nejad; Hossein Khodadadi (Mazandaran University of Medical Sciences, 2023)
Background and Purpose: Candida auris is a multidrug-resistant yeast that rapidly spreads, making it the leading Candidate for the next pandemic. One main leading cause of emerging resistant C. auris isolates is nonsynonymous mutations. This study aimed to detect the Y132F mutation, one of the most important azole resistance-associated mutations in the ERG-11 gene of C. auris, by developing a reliable high-resolution melt (HRM)-based method.Materials and Methods: Five C. auris isolates from Iran, plus three control isolates from other Clades were used in the study. The antifungal susceptibility testing through micro broth dilution was performed to recheck their susceptibility to three azole antifungals,including fluconazole, itraconazole, and voriconazole. Moreover, the polymerase chain reaction (PCR) sequencing of the ERG-11 gene was performed. Following the bioinformatic analysis and HRM-specific primer design, an HRM-based assay was developed and evaluated to detect ERG-11 mutations.Results: The minimum inhibitory concentrations of fluconazole among Iranian C. auris isolates ranged from 8 to 64 μg/mL. The PCR-sequencing of the ERG-11 gene and bioinformatic analyses revealed the mutation of Y132F, a substitution consequence of A to T on codon 395 in one fluconazole-resistant isolate (IFRC4050). The developed HRM assay successfully differentiated the targeted single nucleotide polymorphism between mutant and wild types (Melting temperature [Tm]: 81.79 ℃ - cycle threshold [CT]: 20.06 for suspected isolate). For both mutant and non-mutant isolates, the mean Tm range was 81.79-82.39 °C and the mean CT value was 20.06-22.93. These results were completely in accordance with the findings of DNA sequencing.Conclusion: The fast-track HRM-based method successfully detected one of the most common mechanisms of resistance in the ERG-11 gene of C. auris within 3 h. Finally, the development of more panels of HRM assays for the detection of all azole resistance mutations in C. auris ERG-11 is recommended to expand the scope of the field and facilitate the elaboration of rapid and accurate methods of antifungal resistance assessment.